Oenological traits of Lachancea thermotolerans show signs of domestication and allopatric differentiation. Issue 1 (December 2018) - Hranilovic, Ana; Gambetta, Joanna; Schmidtke, Leigh; Boss, Paul; Grbin, Paul; Masneuf-Pomarede, Isabelle; Bely, Marina; Albertin, Warren; Jiranek, Vladimir
Abstract The yeastLachancea thermotolerans (previouslyKluyveromyces thermotolerans ) is a species of large, yet underexplored, oenological potential. This study delivers comprehensive oenological phenomes of 94 L. thermotolerans strains obtained from diverse ecological niches worldwide, classified in nine genetic groups based on their pre-determined microsatellite genotypes. The strains and the genetic groups were compared for their alcoholic fermentation performance, production of primary and secondary metabolites and pH modulation in Chardonnay grape juice fermentations. The common oenological features ofL. thermotolerans strains were their glucophilic character, relatively extensive fermentation ability, low production of acetic acid and the formation of lactic acid, which significantly affected the pH of the wines. An untargeted analysis of volatile compounds, used for the first time in a population-scale phenotyping of a non-Saccharomyces yeast, revealed that 58 out of 90 volatiles were affected at anL. thermotolerans strain level. Besides the remarkable extent of intra-specific diversity, our results confirmed the distinct phenotypic performance ofL. thermotolerans genetic groups. Together, these observations provide further support for the occurrence of domestication events and allopatric differentiation inL. thermotolerans population.